Difference as an essential teacher in a Them-Us international context: Pre-service teachers' reflections on a university township teaching project. (27th May 2023) - Carter, Jane; Knight, Ben; Vickers-Hulse, Karan
ABSTRACT: This article explores data from a group of British pre-service teachers (PST) following a teaching programme in South Africa. Their reflections are analysed in relation to assertions that such intercultural programmes do little to change hegemonic beliefs about the 'other'. Analysis of questionnaire and interview data suggests that whilst these assertions have some validity, the issues are complex and nuanced. Findings indicate apparent shifts from object-based to relational views of the 'other', though these shifts were not always complete or fully developed. Sitting with uncertainty and discomfort prompted PSTs' critical reflections demonstrating the interactive and dialogic nature of intercultural understanding and provided the pre-requisites for personal and professional development.  We conclude that when appropriately orientated, teaching placements in the global South can encourage critical, relational pedagogies, intercultural understanding and a dialectical relationship with difference which can translate into positive shifts in PST beliefs and practice.